Stem-modules using gamification as induction teaching aids for non-academic tahfiz students / Nor Hanim Abd Rahman ... [et al.] - Abd Rahman, Nor Hanim; Abu Mansor, Siti Nurleena; Saad, Siti Mariam; Yahaya, Syarul Heiry; Omar, Mahanim (Universiti Teknologi MARA, Kedah, 2023)
The absence of academic subjects throughout the three-year of tahfiz memorization may cause the students to lose interest in STEM subjects. As a result, a non-digital game-based module is developed to support their teaching and learning. The main objective of this innovation is to increase students’ interest in STEM subjects, particularly Mathematics, and to equip them with the fundamental foundation prior to returning to upper secondary school. [methodology] This module includes four selected non-digital real-world relatable games: arithmetic-fractions of a cafe and restaurants, geometry puzzle block and draw speed and velocity games of Tic-tac-toe, and strategic-coordinate military game. These games are chosen based on the lower secondary school mathematics curriculum and are introduced to students based on their level of comprehension. This module is applied to Maahad Riyadhil Quran (MRIQ) students during a prescribed program. The uniqueness of this module is that it incorporates cognitive and psychomotor skills for each of the non-digital games, making it an interesting teaching and learning aid to overcome interest gaps in STEM courses for non-academic tahfiz students. This module has positively affected students' interest to comprehend the value of mathematics, as seen by the results. This method, in the students’ opinions, increased their interest in mathematics and widened their perspectives on the topics. Non-digital games have societal potential benefits, such as improving students' engagement by making learning more dynamic, interactive, enjoyable, and at the same time, more challenging. Students are incentivized to participate and strive for excellence, which enhances interest not only in mathematics, but also in retention, motivation, personalized learning, and social interaction. The innovative module has a commercial potential, where workshops or events can be hosted to create enthusiasm and interest among students and parents, while also engaging them in the design process by soliciting their thoughts and opinions to increase excitement and ownership.